Integrated Borehole, Radar, and Seismic Velocity Analysis Reveals Dynamic Spatial Variations Within a Firn Aquifer in Southeast Greenland. Issue 18 (15th September 2020) - Killingbeck, S. F.; Schmerr, N. C.; Montgomery, L. N.; Booth, A. D.; Livermore, P. W.; Guandique, J.; Miller, O. L.; Burdick, S.; Forster, R. R.; Koenig, L. S.; Legchenko, A.; Ligtenberg, S. R. M.; et al.
Abstract: Perennial water storage in firn aquifers has been observed within the lower percolation zone of the southeast Greenland ice sheet. Spatially distributed seismic and radar observations, made ~50 km upstream of the Helheim Glacier terminus, reveal spatial variations of seismic velocity within a firn aquifer. From 1.65 to 1.8 km elevation, shear‐wave velocity ( Vs ) is 1, 290 ± 180 m/s in the unsaturated firn, decreasing below the water table (~15 m depth) to 1, 130 ± 250 m/s. Below 1.65 km elevation, Vs in the saturated firn is 1, 270 ± 220 m/s. The compressional‐to‐shear velocity ratio decreases in the downstream saturated zone, from 2.30 ± 0.54 to 2.01 ± 0.46, closer to its value for pure ice (2.00). Consistent with colocated firn cores, these results imply an increasing concentration of ice in the downstream sites, reducing the porosity and storage potential of the firn likely caused by episodic melt and freeze during the evolution of the aquifer. Plain Language Summary: An integrated geophysical analysis of seismic, radar, and borehole measurements has been completed over a firn aquifer in southeast Greenland. We show the stiffness of the aquifer increases at lower elevations, closer to sea level, which leads to a decrease in pore space for the meltwater to be stored. This corresponds to an increase in ice content within the firn at lower elevations, as observed in borehole measurements, and likely caused by the meltwater refreezing within and below the aquifer. Key Points: Characterizing the storage potential of firn aquifers is important for predicting water budgets in a warming world Multiple geophysical methods are combined to evaluate the elastic properties and porosity of the firn aquifer Seismic velocities detect an increase in ice content in the aquifer downslope, reducing the porosity and storage potential of the firn